2019
DOI: 10.1080/15592324.2019.1659687
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines alleviate the inhibitory effect of the DNA cross-linking agent mitomycin C on root growth

Abstract: Polyamines (putrescine, spermidine and spermine) are ubiquitously present in various types of cells of living organisms. They are involved in a variety of cellular processes, including cell proliferation and cell differentiation, and are required for abiotic stress tolerances in plants. However, it is still not understood whether polyamines are involved in the plant growth inhibition caused by DNA-damaging agents. In this study, we examined the effects of polyamines on the inhibition of plant root growth and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Thus, PAs are essential for different cellular functions, including cell growth and proliferation [9]. Several works have demonstrated that PAs have antioxidative effects [10], can promote homology-directed DNA repair [11], and downregulate DNA damage-associated cell death [12,13]. Almost all cells can produce PAs, but their production is especially high in rapidly growing cells; therefore, the concentration of PAs as well as the gene expression and activity of enzymes involved in PA biosynthesis are higher in cancer tissues than in normal surrounding tissues [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PAs are essential for different cellular functions, including cell growth and proliferation [9]. Several works have demonstrated that PAs have antioxidative effects [10], can promote homology-directed DNA repair [11], and downregulate DNA damage-associated cell death [12,13]. Almost all cells can produce PAs, but their production is especially high in rapidly growing cells; therefore, the concentration of PAs as well as the gene expression and activity of enzymes involved in PA biosynthesis are higher in cancer tissues than in normal surrounding tissues [14][15][16].…”
Section: Introductionmentioning
confidence: 99%